شعر الرباطيات وإثبات الفحولة الشعرية في منطقة وادي سوف دراسة موضوعاتية في نماذج متنوعة - بن علي, محمد الصالح (جامعة الوادي - University of Eloued, 2023)
This study aims to introduce an art that is almost extinct, and is no longer practiced in the field since the forties of the last century, which is the poetry of the Rabatiyat, which is considered one of the important types of popular poetry. Obtaining the title of stallion, without ignoring its various dimensions that reflect the life of the Bedouins in the Wadi Souf region, and its social, economic and anthropological implications of symbols and cultural deposits. ملخص 2 This study aims to revive the poetry of the Rabatiyat and record examples of it, with a proposal to revitalize it in the form of public forums or festivals and the like.
Keywords: Rabatiyat, virility, wedding, well